Top-down biological motion perception does not differ between adults scoring high versus low on autism traits - Oomen, Danna; Wiersema, Jan R.; Orgs, Guido; Cracco, Emiel (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
The perception of biological motion is an important social cognitive ability. Models of biological motion perception recognize two processes that contribute to the perception of biological motion: a bottom-up process that binds optic-flow patterns into a coherent percept of biological motion and a top-down process that binds sequences of body-posture ‘snapshots’ over time into a fluent percept of biological motion. The vast majority of studies on autism and biological motion perception have used point-light figure stimuli, which elicit biological motion perception predominantly via bottom-up processes. Here, we investigated whether autism is associated with deviances in the top-down processing of biological motion. For this, we tested a sample of adults scoring low vs high on autism traits on a recently validated EEG paradigm in which apparent biological motion is combined with frequency tagging (Cracco et al., 2022) to dissociate between two percepts: 1) the representation of individual body postures, and 2) their temporal integration into movements. In contrast to our hypothesis, we found no evidence for a diminished temporal body posture integration in the high-scoring group. We did, however, find a group difference that suggests that adults scoring high on autism traits have a visual processing style that focuses more on a single percept (i.e. either body postures or movements, contingent on saliency) compared to adults scoring low on autism traits who instead seemed to represent the two percepts included in the paradigm in a more balanced manner. Although unexpected, this finding aligns well with the autism literature on perceptual stability.
Keywords: EEG Frequency Tagging; Apparent biological Motion; Autism